Study of amino acid composition of Lychnis coronaria raw materials - Polishchuk, Yuliia; Burda, Nadiia (Annals of Mechnikov’s Institute, 2022)
Introduction. Lychnis coronaria (L.) Murray ex Desr. is a perennial herbaceous plant in the Caryophyllaceae family. The plant is cultivated in many countries of the world, in particular in Ukraine, as a decorative plant. Various parts of Lychnis coronaria are used in traditional medicine around the world to treat leprosy, diarrhea, hemorrhoids, lung and liver diseases. In addition, the raw materials have anti-inflammatory activity. Today, Lychnis coronaria is studied by scientists from many countries. For example, recent studies conducted by Indian scientists have shown the anti-asthmatic effect of Lychnis coronaria due to the reduction of bronchial hyperreactivity, as well as cellular and molecular markers of airway inflammation and immunity. In addition, Romanian scientists proposed and researched a complex herbal remedy, which included Lychnis coronaria. Pronounced antimicrobial and antioxidant activity has been established for this medicinal product. Indian scientists have established an antihepatotoxic effect for a water extract from the herb Lychnis coronaria. Regarding the pharmacological activity of amino acids, Chinese scientists have conducted research on the study of the combination of natural compounds with amino acids, in particular valine and proline. It was found that the obtained derivatives promoted a higher proliferation rate in HepG2 cells than the natural compounds before derivatization. This indicated that these derivatives have improved hepatoprotective ability. Other studies conducted by UK scientists have shown interesting results regarding the effect of amino acids on the prevention and treatment of bronchial asthma. Because amino acids contribute to a variety of antioxidant and immunological activities relevant to the pathogenesis of asthma, scientists have hypothesized that differences in amino acids may be involved in the etiology of asthma. As a result of the conducted experiments, it was established that high levels of cystine introduced into the plasma do not have a protective effect on the risk of developing bronchial asthma, but for glycine this correlation can be traced, therefore it requires further study. Therefore, the above information makes it possible to assume that amino acids can indirectly affect the manifestation of the pharmacological activity of Lychnis coronaria raw materials. For this purpose, it is rational to conduct a study of the amino acid composition of the raw materials of the studied plant, which became the purpose of this work. Materials and methods. Leaves, flowers and stems of Lychnis coronaria were used for the study. The raw material was harvested during the flowering period in 2020-2021 in the Kharkiv region. The determination of the qualitative composition and quantitative content of amino acids in the raw material was carried out by ion-exchange chromatography using an automatic amino acid analyzer ААА Т-339М. The study of amino acids was performed after prehydrolysis with hydrochloric acid. To this end, 6 N hydrochloric acid solution was added to the test tube with exactly measured portion of herb and after that the tube was cooled in a liquid nitrogen flow. When the test tube contents were frozen, the air was removed from it under vacuum to avoid amino acid oxidation. Then the test tube was sealed and preserved in thermostat at a constant temperature of 106˚С within 24 hours. Then the test tube contents were cooled, totally transferred to a glass weighing box, and hydrochloric acid was evaporated on a water bath. 3-4 ml of deionized water was added to a dried sample, and the evaporation went on. The obtained sample was dissolved in 0.3 N lithium citrate buffer at pH 2.2 and applied on amino acid analyzer ion exchange column, whose cation exchanger was previously equalized with sodium citrate or lithium citrate buffer solution. Research results. As a result of the conducted experiment, 18 amino acids were identified in all types of studied raw materials, and their quantitative content was also determined. The highest content of the total amount of amino acids was observed in Lychnis coronaria flowers (9.87%), the lowest – in the stems (3.72%). Regarding the leaves of the studied plant, the content of amino acids was slightly higher than the content of this class of compounds in the stems. The same trend was observed in the analysis of the amount of essential amino acids, their predominance was noted in the flowers of Lychnis coronaria (3.57%). It should be noted that in all studied types of raw materials, aspartic and glutamic acids prevailed in terms of content. It is known that these amino acids are used in diseases of the cardiovascular and central nervous systems. As for glycine, information about its effect on the prevention and treatment of bronchial asthma is given in the introduction, compared to leaves and stems, its content in flowers was the highest (0.62%) versus 0.40% and 0.21%, respectively. Regarding proline and valine, their content dominated in Lychnis coronaria flowers. However, it should be noted that the proline content in flowers was significantly higher (0.82%) than the content in leaves and stems – 0.15% and 0.27%, respectively. Thus, the conducted research can form the basis for further experiments related to the study of pharmacological Lychnis coronaria. In addition, based on the content of amino acids, it is possible to single out the more promising types of Lychnis coronaria raw materials for further research - flowers and leaves. Conclusions. Therefore, the obtained experimental data regarding the study of the amino acid composition of Lychnis coronaria raw materials deepens the knowledge about the chemical composition of this plant. Also, these results can be used in the future in the study of the pharmacological activity of Lychnis coronaria raw materials. Keywords: Lychnis coronaria, amino acid composition.